Antimicrobial stewardship challenges: A bibliometric analysis - Haris, Ananda; Aini, Qurratul (Future Science, 2024)
Antimicrobial resistance (AMR) is a worldwide problem that presents a substantial risk to the healthcare of the general population. Antimicrobial stewardship (AMS) is essential in hospitals to optimize the use of antimicrobial agents and address the challenges of drug resistance, superinfection, and rising healthcare costs. However, there are still many obstacles in the implementation of the antimicrobial stewardship program (ASP) in hospitals and healthcare, so the decline in AMR to date is still not in line with expectations. The purpose of this study is to analyze antimicrobial stewardship research trends and to determine the progress of antimicrobial stewardship research in hospitals or healthcare. This study is qualitative research with a literature study approach. Taken from the Scopus database in the last five years, 534 articles were obtained to be analyzed using Mapchart, VOSviewer, and Rstudio-Biblioshiny. The results show that implementation of AMS is still widely studied from year to year. Research trends show the success of AMS in overcoming AMR, the barriers that occur during implementation, and the factors that contribute to the running of the AMS program. The findings also show authors, countries that publish the most, journals that are most cited, topics that are rarely published, and themes that can be developed in the future. The conclusion of this study is to determine the development of AMS research and to gain a better understanding of AMP implementation.